Comparative Evaluation of DNA Damage in SARS-CoV-2 Infected Patients with and Without Type 2 Diabetes Using Comet Assay - Ibrahem, Osamah Imad; Karomi, Asma Sumiea (Journal of Neonatal Surgery, 2025)
SARS-CoV-2, the virus that causes COVID-19, is a virus with a widespread systemic effect, not just on the respiratory system. Its most prominent effects include the ability to induce DNA damage as a result of oxidative stress and chronic inflammation. These effects are more severe in individuals with metabolic diseases such as type 2 diabetes mellitus (T2DM), where cellular damage is exacerbated. The study included the analysis of 22 control and 72 blood samples from COVID-19 patients confirmed using RT-PCR, including 43 patients with type 2 diabetes and 29 non-diabetic patients. Samples were collected from Kirkuk General Hospital and Azadi Teaching Hospital in Iraq. The Comet assay was performed to measure DNA damage, and the results were analyzed using TriTek Comet Score v2.0.0.38 software, where damage was expressed as the percentage of DNA in tail. Statistical analyses were performed using a t-test to verify the significance of differences between groups. The results of the Comet test showed that the diabetic group exhibited the highest percentage of DNA damage (38.03 ± 6.40%), followed by the non-diabetic COVID-19 group (3.06 ± 1.73%), and then the control group (1.71 ± 1.12%). The differences between the diabetic group and the other two groups were highly statistically significant (p < 0.001), while no significant differences were recorded between the non-diabetic group and the control group (p > 0.05). The results indicate that type 2 diabetes significantly contributes to the increased impact of COVID-19 on DNA damage, likely due to increased systemic inflammation and oxidative stress. These findings underscore the importance of glycemic control and early intervention to reduce genetic complications resulting from the virus